Відновлення електробуріння в Україні - Червінський, Володимир Петрович; Мельник, Роман Юрійович (НТУ "ХПІ", 2018)
У статті наведені відомості про історію виникнення електробурів і їх використання, наведено порівняння електробуріння з турбінно-роторним бурінням у певному районі, розглянуті особливості конструкції електробура, компонування низу бурової колони при бурінні електробуром. Наведені технічні дані деяких типів електробура, детально розглянуті основні переваги та недоліки у використанні електробура. Наприкінці автори висловлюють думку стосовно перспектив у використанні електробуріння, зокрема в Україні.

The article gives information about the history of the occurrence of electodrills and their use, a comparison of drilling with turbine rotor drilling in a certain area is given, features of the electrodrill construction, layout of the bottom of the drill column during drilling with electrodrill are considered. The technical data of some types of electrodrills are given, the main advantages and disadvantages of electrodrill are considered in detail. In the end, the authors express an opinion on the prospects for the use of electrodrill particularly in Ukraine.
Returning of electrodrilling in Ukraine
Keywords: електробур; буріння; бурільні труби; горизонтально-спрямовані свердловини; асинхронний двигун; бурова колона; electrodrill; drilling pipes; wells; asynchronous motor; drill column; horizontal directional wells